Status of Women in Islam and the Present Indian Scenario - Siddiqa, Aisha; Ruby, Ruby (ASPENSI, 2018)
ABSTRACT: This paper, based on qualitative study, focuses on the status of women in Islam and the present Indian scenario. The status of women in Islam is very high, where they are considered equal to men; but the women of the minority community suffer from the dual handicap of being women and belonging to minority community in India. Muslim women are suffering, from both internal and external oppression. Muslim men practice what they themselves believe is Islamic and oppress their women, and refuse to entertain any thought of change. They degrade women and in most cases violate their rights by dictating them. Many Muslim women also believe that Islam enslaves them, because they have not listened to what is written in the Al-Qurâan. The Al-Qurâan liberates women and has given them equal status to men. Since the rural section of Indian society does not know what is written in the Al-Qurâan or Al-Hadith, they tend to follow the âimamâ of their mosque, who himself comes from a poor family and in most cases has very limited knowledge of theology and Islamic âshariahâ or law. The present study is concerned with four different areas of womenâs life: (1) the private life, i.e. status in the family; (2) female education; (3) marriage and divorce; and (4), lastly, the practical life, i.e. employment and job opportunities. All these four areas are discussed the problems and concerns related to Muslim women in India, and what are their rights according to Islam. This study is a step in direction of eradicating misunderstanding and correcting the wrongs in prevalence. KEY WORD: Status of Women in Islam; Muslim Women in India; Al-Qurâan and Al-Hadith, Cultural Tradition; Eradicating Misunderstanding.Â ABSTRAKSI: âStatus Perempuan dalam Islam dan Skenario dari India Sekarangâ. Makalah ini, berdasarkan studi kualitatif, berfokus pada status perempuan dalam Islam dan skenario dari India sekarang. Status perempuan dalam Islam sangat tinggi, di mana mereka dianggap setara dengan laki-laki; namun perempuan dari komunitas minoritas menderita kegagalan ganda, karena menjadi perempuan dan termasuk dalam komunitas minoritas di India. Wanita Muslim menderita, baik oleh penindasan internal maupun eksternal. Pria Muslim mempraktekan apa yang mereka percayai sendiri tentang Islam dan menindas wanita, serta menolak untuk memikirkan perubahan apapun terhadap wanita. Mereka menurunkan derajat perempuan dan dalam kebanyakan kasus melanggar hak mereka dengan mendikte para wanita. Banyak wanita Muslim juga percaya bahwa Islam memperbudak mereka, karena mereka tidak mendengarkan apa yang tertulis dalam Al-Quran. Al-Quran membebaskan wanita dan memberi mereka status yang setara dengan pria. Karena sebagian masyarakat pedesaan India tidak tahu apa yang tertulis dalam Al-Quran atau Al-Hadits, mereka cenderung mengikuti âimamâ masjid, yang berasal dari keluarga miskin dan dalam kebanyakan kasus sangat terbatas pengetahuan tentang teologi dan syariah Islam. Kajian ini berkaitan dengan empat bidang kehidupan perempuan yang berbeda: (1) kehidupan pribadi, yaitu status dalam keluarga; (2) pendidikan perempuan; (3) pernikahan dan perceraian; dan (4), terakhir, kehidupan praktis, yaitu pekerjaan dan peluang kerja. Semua empat bidang tersebut dibahas masalah dan hal-hal yang terkait dengan wanita Muslim di India, serta apa hak mereka menurut Islam. Penelitian ini merupakan langkah menuju pemberantasan kesalahpahaman dan koreksi terhadap kesalahan dalam kelaziman. KATA KUNCI: Status Perempuan dalam Islam; Wanita Muslim di India; Al-Quran dan Al-Hadits, Tradisi Budaya; Memberantas Kesalahpahaman.Â Â About the Authors: Aisha Siddiqa and Ruby are the Research Scholars at the Department of Education AMU (Aligarh Muslim University) in Uttar Pradesh, India. For academic interests, the authors are able to be contacted via e-mail at: aisha.siddiqa1@gmail.comSuggested Citation: Siddiqa, Aisha & Ruby. (2018). âStatus of Women in Islam and the Present Indian Scenarioâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Volume 3(1), February, pp.1-12. Bandung, Indonesia and BS Begawan, Brunei Darussalam: Minda Masagi Press owned by ASPENSI and BRIMAN Institute, ISSN 2443-1776. Article Timeline: Accepted (March 15, 2017); Revised (October 9, 2017); and Published (February 28, 2018).